2010
DOI: 10.1029/2009jc006070
|View full text |Cite
|
Sign up to set email alerts
|

What determines the maximum sea ice extent in the Sea of Okhotsk? Importance of ocean thermal condition from the Pacific

Abstract: [1] Previous studies suggested that the interannual variability of the maximum sea ice extent (MSIE) in the Sea of Okhotsk is not explained only by atmospheric conditions. In this study, we examined the effect of the ocean thermal condition on the determination of the MSIE based on observational data. We found that the MSIE is highly correlated with the sea surface temperature (SST) and ocean temperature around the East Kamchatska Current (EKC) in the Pacific in late autumn (November-December). The significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
(44 reference statements)
1
15
0
Order By: Relevance
“…1) and the central and eastern Sea of Okhotsk are considered as such cases. In the central and eastern Sea of Okhotsk, relatively warm water that originates from the East Kamchatka Current comes from the North Pacific through the northern Kuril Straits (Ohshima et al 2010). 2b).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…1) and the central and eastern Sea of Okhotsk are considered as such cases. In the central and eastern Sea of Okhotsk, relatively warm water that originates from the East Kamchatka Current comes from the North Pacific through the northern Kuril Straits (Ohshima et al 2010). 2b).…”
Section: Resultssupporting
confidence: 55%
“…1), coastal polynyas are formed by divergent ice drift associated with prevailing cold offshoreward wind (Martin et al 1998). Nakanowatari et al (2007) suggested that, during the past 50 yr, warming of the intermediate water and weakening of the overturning have occurred in the northwestern North Pacific, originating from the Sea of Okhotsk. Nakanowatari et al (2007) suggested that, during the past 50 yr, warming of the intermediate water and weakening of the overturning have occurred in the northwestern North Pacific, originating from the Sea of Okhotsk.…”
Section: Sea Ice and Its Role In The Sea Of Okhotskmentioning
confidence: 99%
“…26 we plot the lag correlation maps between the sea ice extent of the Okhotsk Sea in March and SST in the preceding October to December. As shown by Nakanowatari et al (2010), the correlation maps indicate that SST off the east coast of Kamchatka Peninsula in autumn has a large negative correlation with the sea ice extent in the subsequent winter. It is also worth emphasizing that the area with high correlation coefficients in FORA, which is confined along EKC compared to the maps in Nakanowatari et al (2010), moves southwestward along EKC and a part of the correlation signal enters the southeastern part of the Okhotsk Sea through straits along the Kuril Islands, where there is large interannual variability in the sea ice extent.…”
Section: Sea Ice In the Okhotsk Seamentioning
confidence: 90%
“…It is also worth emphasizing that the area with high correlation coefficients in FORA, which is confined along EKC compared to the maps in Nakanowatari et al (2010), moves southwestward along EKC and a part of the correlation signal enters the southeastern part of the Okhotsk Sea through straits along the Kuril Islands, where there is large interannual variability in the sea ice extent. These features in FORA support a hypothesis proposed by Nakanowatari et al (2010) that the interannual variability of the sea ice extent in the Okhotsk Sea is influenced by advection of temperature anomalies by EKC.…”
Section: Sea Ice In the Okhotsk Seamentioning
confidence: 99%
See 1 more Smart Citation